2008
DOI: 10.1501/vetfak_0000000298
|View full text |Cite
|
Sign up to set email alerts
|

Bafra koyunlarında bazı meme özellikleri ve kuzularda büyüme ile bu özelliklerin farklı süt kontrol yöntemleriyle tespit edilen süt verimi ve sağım özellikleriyle fenotipik korelasyonları

Abstract: Özet: Bu araştırmada, Bafra koyunlarında bazı meme özellikleri ve kuzularda büyüme ile bu özelliklerle farklı süt kontrol yöntemleriyle tespit edilen süt verimi ve sağım özellikleri arasındaki ilişkiler incelenmiştir. Araştırma, 2006 yılında Gökhöyük Tarım İşletmesi'nde (Amasya) yürütülmüştür. Veriler 2 ve 3 yaşlı, ikiz kuzu doğurmuş ve rasgele seçilen 70 koyun ile 40 ikiz kuzudan elde edilmiştir. Koyunlar rasgele üç gruba (Tart-Emzir-Tart (TET) Grubu, Oksitosin + Makineli Sağım (OMS) Grubu, Makineli Sağım (MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It was informed that some polymorphisms of INHBB in some sheep breeds were related with multiple births and it was declared that INHBB gene might be a candidate gene effecting on litter size [13] . Bafra sheep breed derived from two Turkish native sheep breeds, Sakiz and Karayaka, has high prolificacy coming from Sakiz sheep breed [14,15] . It was indicated that the litter size of Bafra ewes was between 1.78 and 2.20 [14,15] while the litter size of Akkaraman ewes was between 1.20 and 1.30 [16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was informed that some polymorphisms of INHBB in some sheep breeds were related with multiple births and it was declared that INHBB gene might be a candidate gene effecting on litter size [13] . Bafra sheep breed derived from two Turkish native sheep breeds, Sakiz and Karayaka, has high prolificacy coming from Sakiz sheep breed [14,15] . It was indicated that the litter size of Bafra ewes was between 1.78 and 2.20 [14,15] while the litter size of Akkaraman ewes was between 1.20 and 1.30 [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Bafra sheep breed derived from two Turkish native sheep breeds, Sakiz and Karayaka, has high prolificacy coming from Sakiz sheep breed [14,15] . It was indicated that the litter size of Bafra ewes was between 1.78 and 2.20 [14,15] while the litter size of Akkaraman ewes was between 1.20 and 1.30 [16] .…”
Section: Introductionmentioning
confidence: 99%